Two experimental fish aggregating systems (fads) in the Aegean sea: their design and application - Aytaç Özgül (Brazilian Journal of Oceanography, 2011)
Two steel spar buoys were constructed and moored in 50 and 100 m deep of water in the Aegean Sea to support recreational fisheries. The first FAD was deployed at coordinates 38°01´48´´N 26°58´02´´E and at a distance of 3 nautical miles from the shoreline. The other FAD was moored at 1.1 nautical miles from the shoreline at coordinates 38°03´11´´N; 26°59´01´´E. An anchor (1.2x1.2x0.8 m3) weighing approximate 2.76 metric ton, made of reinforced concrete, was used to hold a FAD weighing approximate 1.5 metric ton. Hardware and connections of FADs, ropes, mooring calculation and anchor design were made. The interaction between the forces of wave and current and FADs in those waters was investigated. In the experiment, all forces (drag force, buoyancy force etc.) acting on FADs were calculated. It is proposed that the construction of the FADs should take the following design criteria into consideration: wave and current, forces related to the FADs, deployment depth, mooring hardware and ropes. This knowledge provides an important reference for stakeholders performing projects aiming to increase the performance and service life FADs. Duas bóias de aço spar foram construídas e ancoradas em 50 e 100 m de profundidade nas águas do Mar Egeu para dar apoio à pesca recreativa. O primeiro FAD foi implantado nas coordenadas 38°01'48''N 26°58'02''E, a uma distância de 3 milhas náuticas da costa. O outro ficou ancorado a 1,1 milha náutica da costa nas coordenadas 38°03'11''N; 26°59'01''E. Uma âncora (1.2x1.2x0.8 m3), pesando aproximadamente 2,76 toneladas, feita de concreto armado, foi usada para prender um FAD de peso aproximado de 1,5 toneladas. Foram realizados cálculos para determinação das conexões dos FADs, dos cabos e da ancoragem. A interação entre as forças de ondas e correntes com os FADs foi também investigada. No experimento, todas as forças (força de arrasto, força de empuxo, etc) atuantes sobre os FADs foram calculadas. É proposto que para a construção dos FADs deverão ser levados em consideração os seguintes fatores: ondas e correntes, forças relacionadas com os FADs, profundidade de implantação, sistema computacional dos moorings e cordas de amarração. Esse conhecimento proporcionará referência importante para os interessados em realizar projetos que visem aumentar o desempenho e a vida útil dos FADs.